Remote Optogenetics Using Up/Down-Conversion Phosphors - Matsubara, Takanori; Yamashita, Takayuki (Frontiers in Molecular Biosciences, 2021)
Microbial rhodopsins widely used for optogenetics are sensitive to light in the visible spectrum. As visible light is heavily scattered and absorbed by tissue, stimulating light for optogenetic control does not reach deep in the tissue irradiated from outside the subject body. Conventional optogenetics employs fiber optics inserted close to the target, which is highly invasive and poses various problems for researchers. Recent advances in material science integrated with neuroscience have enabled remote optogenetic control of neuronal activities in living animals using up- or down-conversion phosphors. The development of these methodologies has stimulated researchers to test novel strategies for less invasive, wireless control of cellular functions in the brain and other tissues. Here, we review recent reports related to these new technologies and discuss the current limitations and future perspectives toward the establishment of non-invasive optogenetics for clinical applications.